Tantangan dan Strategi Pengelolaan Sumber Daya Manusia Pada Lembaga Pendidikan - m.nur, Yusaini; Prakoso, Wahyu Adi; Sulastri3, Sulastri3 (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2023)
This article discusses the challenges in managing human resources (HR) and HR management strategies in educational institutions. The term